The relationship between self-esteem and mobile phone addiction among college students: The chain mediating effects of social avoidance and peer relationships - Chen, Chunmei; Shen, Yuanyi; Lv, Shuai; Wang, Bo; Zhu, Yujie (Frontiers in Psychology, 2023)
Mobile phone addiction has a negative impact on the physical and mental health of college students, which has attracted extensive attention from scholars. Numerous studies have explored the influence of self-esteem on mobile phone addiction, but few have focused on the chain mediating effects of social avoidance and peer relationships. Mobile phone addiction brings many negative effects on the physical and mental health of college students, which is detrimental to their growth and success. In this study, we investigated the mechanism of the influence of self-esteem on mobile phone addiction among 694 college students using the Self-Esteem Scale, the Mobile Phone Addiction Scale, the Peer Relationship Scale and the Social Avoidance and Distress Scale. The results showed that (1) self-esteem significantly and negatively predicted mobile phone addiction; (2) self-esteem influenced mobile phone addiction through the mediating effect of social avoidance; (3) self-esteem influenced mobile phone addiction through the mediating effect of peer relationships; and (4) social avoidance and peer relationships played a chain mediating role in the influence of self-esteem on mobile phone addiction. These findings can help researchers and educators better understand the underlying mechanisms of the relationship between self-esteem and mobile phone addiction and to provide practical and effective operational suggestions for the prevention and intervention of mobile phone addiction among college students.